Saturated-unsaturated seepage analysis considering uncertain permeable properties information - Ohno, K. (Mie Univ., Tsu (Japan). Faculty of Bioresources) (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1993)
For the sake of developing a finite element method, it has been easy to carry out a saturated-unsaturated seepage analysis. However, permeable properties in saturated zone and unsaturated zone have to be known. To know the permeable property in a saturated zone is less of a problem than to know permeable properties in an unsaturated zone. However, to find out the permeable property in a saturated zone has many problems because of the uncertainties involved in measuring, designing and construction. To know permeable properties in an unsaturated zone have a great deal more uncertainties. To consider uncertainties, permeable properties in saturated and unsaturated zone should be defined by the fuzzy sets which have widths and membership value. Also, observational constructions are important in dealing with these uncertainties. Back analysis, utilizes the fuzzy theory, has been already developed. Back analysis searches for the permeable properties in the saturated and unsaturated zone. The properties sought for are defined by the fuzzy sets.So, saturated-unsaturated seepage analysis which can utilize fuzzy information is needed to perform observational constructions. The analysis is developed here. The developed analysis uses the concept of level sets and the extended principle in the fuzzy theory. An experiment was performed to denote the validity of the developed analysis. The experiment used two kinds of glass beads. Two layers are made by the beads. The permeable properties of the beads are obtained by the back analysis utilizing the fuzzy theory. The seepage experiment was performed through the layers. The experimental results were compared with the results computed by the developed analysis. The comparison was in good agreement. This means that the back analysis and seepage analysis developed here are valid.